2012
DOI: 10.2134/agronj2011.0382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Planting Date on Soybean Growth, Yield, and Grain Quality: Review

Abstract: Delayed planting date and unfavorable environmental conditions have a negative effect on soybean [Glycine max (L.) Merr.] growth, development, and yield. Changes in photoperiod, temperature, and precipitation with delayed planting affect the duration of vegetative and reproductive stages, number of branches and pods, plant height, leaf area index (LAI), and normalized difference vegetation index (NDVI), and hence the grain yield. Delayed planting can also affect the soybean seed quality by changing the oil and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 95 publications
3
71
1
5
Order By: Relevance
“…As for the cultivars, C2 was statistically superior to C1 in every variable analyzed. However, differences between both seasons and cultivars were found, which supports the hypothesis of the influence of sowing date, due to changes in climatic elements and the length of the crop cycle (Chen and Wiatrak, 2010;Hu and Wiatrak, 2012). Furthermore, climatic elements and the cycle of each cultivar are related to physiological processes of the plants.…”
Section: Unfolding Of the Interaction C × Ssupporting
confidence: 76%
“…As for the cultivars, C2 was statistically superior to C1 in every variable analyzed. However, differences between both seasons and cultivars were found, which supports the hypothesis of the influence of sowing date, due to changes in climatic elements and the length of the crop cycle (Chen and Wiatrak, 2010;Hu and Wiatrak, 2012). Furthermore, climatic elements and the cycle of each cultivar are related to physiological processes of the plants.…”
Section: Unfolding Of the Interaction C × Ssupporting
confidence: 76%
“…A better understanding of crop yield physiology would help to achieve the rates of yield improvement required in the near future. Various authors have published the results of growth analysis on various crops in terms of different management practices and cultivar comparisons, including maize (e.g., Bullock et al, 1993), wheat (Davidson and Campbell, 1984;Barneix, 1990;Karimi and Siddique, 1991;Ozturk et al, 2006;Neugschwandtner et al, 2015), triticale (Royo and Blanco, 1999), Bermuda grass (Silva et al, 2016), soybean (Clawson et al, 1986;Yusuf et al, 1999;Hu and Wiatrak, 2012), potato (Oliveira et al, 2016), sugar beet (Hoffman and KlugeSeverin, 2011) and peas (Silim et al, 1985;Munier-Jolain et al, 2010;Neugschwandtner et al, 2013). However, few studies appear to have been made on the effect of agronomic treatments on the growth and productivity of wheat at both the individual plant and plant stand levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, , 2231-5209 (Online) All Rights Reserved © Applied and Natural Science Foundation www.jans.ansfoundation.org it is also necessary to study the genotype × environment interaction to identify the varieties which are stable in different environments (Calvino et al, 2003a). Sowing dates influence soybean growth stages, due to variation in photoperiod (Han et al, 2006;Kumudini et al, 2007), air temperature (Chen and Wiatrak, 2010), and rainfall distribution and amount during the crop cycle (Hu and Wiatrak, 2012). Meotti et al (2012) observed that 77 % of soybean yield variability was associated with the climate conditions induced by the sowing dates.…”
Section: Introductionmentioning
confidence: 99%